Artificial intelligence in improving the outcome of surgical treatment in colorectal cancer - Avram, Mihaela Flavia; Lazăr, Daniela Cornelia; Mariş, Mihaela Ioana; Olariu, Sorin (Frontiers in Oncology, 2023)
A considerable number of recent research have used artificial intelligence in the area of colorectal cancer (CRC). Surgical treatment of CRC still remains the most important curative component. Artificial intelligence in CRC surgery is not nearly as advanced as it is in screening (colonoscopy), diagnosis and prognosis, especially due to the increased complexity and variability of structures and elements in all fields of view, as well as a general shortage of annotated video banks for utilization. The aim of this minireview is to summarize up to date information on the possibility of using AI in improving the outcome of surgical treatment of CRC. The intraoperative steps which, at this moment, can benefit from AI in CRC are: phase and action recognition, excision plane navigation, endoscopy control, real-time circulation analysis and knot tying. This minireview also analyses the current advances in robotic treatment of CRC as well as the present possibility of automated CRC robotic surgery.